Characteristics of Traditional Human Settlement Landscapes on Bedrock Islands in Guangdong Based on the “Ao” Unit - Ying PAN; Linxi CHEN; Ying SHI (Fengjing Yuanlin)
ObjectiveThe objective of this research is to contribute to the strategic goal of transforming China into a strong maritime nation by enhancing the understanding and management of the ocean, and by fostering innovation in marine science and technology. The exploration and protection of islands, which are increasingly recognized as a new frontier for bolstering comprehensive national power and securing strategic advantages. The sustainable development of islands is intricately linked to the proper handling of the interplay among “people, land, and sea”. This endows the research on human settlement landscapes on islands and their characteristics with significant importance. Geologically, islands are categorized into Bedrock islands, Accumulation islands, Volcanic islands and Coral islands. Bedrock islands possess unique natural environmental attributes that have shaped a distinctive interaction pattern among people, land, and sea. This research zeroes in on the traditional human settlement landscape on bedrock islands in Guangzhou, aiming to elucidate the characteristics of these traditional landscapes and the patterns of human settlement development with “Ao” as the fundamental unit. The research endeavors to uncover the intricate dynamics that have shaped the human settlement landscapes on these islands and to identify the developmental patterns that have emerged over time. By doing so, the research seeks to offer a valuable reference for the conservation and sustainable development of islands, so as to help ensure that they remain vibrant and resilient in the face of environmental and socio-economic challenges.MethodsThis research takes Nan’ao Island in Shantou City as an example to explore the characteristics of traditional human settlement landscapes. The research methodology is based on a comprehensive approach that integrates historical literature review and extensive field surveys. Through this approach, a robust database of the Ao units on Nan’ao Island is meticulously compiled, encompassing information such as location, area, industry type, historical background, cultural beliefs, and origins of the island’s immigrants. The research employs an interdisciplinary framework drawing on insights from human settlement science, marine geography, and marine anthropology. This multifaceted approach provides a nuanced understanding of the island’s landscape. To analyze the spatial and structural aspects of the traditional human settlement landscape, the research utilizes ArcGIS analysis software, which enables a detailed examination of the island’s area and Ao units. This combination of research paradigms and advanced analytical tools aims to uncover the mechanisms that have shaped the traditional human settlement landscape on Nan’ao Island over time.ResultsResearch results are summarized as follows. 1) The components and basic attributes of the Ao unit, the fundamental human settlement unit for the development of Bedrock Island, have been clarified. The Ao unit has the following basic characteristics, backed by hills and facing the bay, with a certain area of flat land between the mountains and the sea, where a large number of island villages and towns are gathered, with complete production and living space. 2) At the island-wide level, the Ao unit has been the preferred area for human settlement on Nan’ao Island, with settlements primarily established around these units. The dominant industries, such as fishing and trade, are closely tied to both the Ao units and their coastal locations, making them focal points for village and town settlements. This illustrates the interaction and coupling between the natural environment and human settlement. 3) At the human settlement unit level, each Ao unit has developed distinctive landscape characteristics influenced by factors such as natural geography, industrial conditions, resource accessibility, transportation, and the strategic needs of different dynasties. These factors have given birth to unique settlement characteristics regarding disaster-prevention landscapes, production landscapes, and the scales of settlements. Four development paths for the Ao units have emerged: Comprehensive development, military-influenced development, fishery-led development, and agriculture-led development. These reflect the residents’ wisdom in strategically arranging settlements based on local conditions, and managing the orderly development of bedrock island communities.ConclusionThe Ao unit, which encapsulates the essential elements of mountain, sea, and human settlement, is recognized as the fundamental residential unit on bedrock islands. This unit has been the cornerstone of the traditional human settlement landscape on Nan’ao Island for millennia. Over time, the island’s landscape has evolved, fostering a harmonious approach to settlement and adaptive landscape strategies centered around the Ao unit. This research examines the Ao unit as a critical lens to understand the development patterns and landscape configuration characteristics of bedrock islands. By analyzing the Ao unit, the research elucidates the key characteristics of human landscapes on such islands and proposes innovative operational approaches for the comprehensive protection and management of island landscapes. These approaches aim to ensure the sustainability while preserving the unique cultural heritage of the islands for future generations. In the future, when island construction is carried out, sustainable development of islands can be promoted through the wisdom of land-based layout and orderly development. The findings of this research are academically significant and hold practical implications for the planning and conservation of island ecosystems.